Keberartian Pendidikan Formal dalam Proses Self-Socialization Remaja Dalam Era Digital Pada Abad 21 - Lisye Salamor (Program Studi Bimbingan dan Konseling, Universitas Pattimura, 2018)
Changes in society and culture affect youth as part of society. The digital age of the 21st century has contributed enormously to the development of human resources, but from these advances, it also plays a negative impact on the development of human resources, especially adolescents in their development. The virtue of self-socialization in adolescents toward the negative is a shared responsibility between the school as a formal education institution and the family. Partnership in developing youth resources between these two community institutions is very important for the achievement of educational goals in adolescent self-development.